2013
DOI: 10.1186/1735-2746-10-21
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of alachlor in liquid and soil cultures under variable carbon and nitrogen sources by bacterial consortium isolated from corn field soil

Abstract: Alachlor, an aniline herbicide widely used in corn production, is frequently detected in water resources. The main objectives of this research were focused on isolating bacterial consortium capable of alachlor biodegradation, assessing the effects of carbon and nitrogen sources on alachlor biodegradation and evaluating the feasibility of using bacterial consortium in soil culture. Kavar corn field soil with a long history of alachlor application in Fars province of Iran has been explored for their potential of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Dehghani et al demonstrated that this phenomenon may be related to atrazine photo degradation when its exposure time to the UV-A radiation is increased, and that a greater oxidation reaction occurs in the presence of hydroxyl radicals (32). In fact, the reaction rate at equilibrium reached a plateau.…”
Section: Effect Of Reaction Time On Atrazine Removalmentioning
confidence: 99%
“…Dehghani et al demonstrated that this phenomenon may be related to atrazine photo degradation when its exposure time to the UV-A radiation is increased, and that a greater oxidation reaction occurs in the presence of hydroxyl radicals (32). In fact, the reaction rate at equilibrium reached a plateau.…”
Section: Effect Of Reaction Time On Atrazine Removalmentioning
confidence: 99%
“…Bacillus subtilis in a soil-slurry system exhibited the maximum removal efficiency with the highest influence on its biological activity. The pH is one of the important parameters affecting cells' metabolism and enzymes function (Dehghani M. et al, 2013). So, pH variations during the incubation period are indicative of biological reactions.…”
Section: The Variation Of Ph During N-hexadecane Biodegradationmentioning
confidence: 99%
“…Bioremediation is a remedial approach treating the contaminated soil with the advantages of simplicity, costeffective and environmentally friendly technology (Vidali M., 2001;Dehghani M. et al, 2013;Wang S. et al, 2016). But this method has some disadvantages such as long treatment time (Cha D.K.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It undergoes weak sorption in soil (organic carbon normalized adsorption coefficient K OC = 33-742 cm 3 g -1 , Wauchope et al, 1992) and can leach to surface water and groundwater (Spalding et al, 2003;Vryzas et al, 2012). Alachlor can undergo chemical decomposition (Chou, 1977) and photodegradation in soil (Fang, 1979), but microbial degradation DT 50 -50% disappearance time) (Tomlin, 2006) has the greatest practical relevance (Dehghani et al, 2013). Bentazone is a benzothiadiazine herbicide for controlling dicotyledonous weeds.…”
Section: Introductionmentioning
confidence: 99%